First-Line Treatment for Advanced Pancreatic Cancer - Oberstein, Paul E; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Pancreatic adenocarcinoma remains a treatment-refractory cancer. Although pancreatic adenocarcinoma is only the 10th most common cause of new cancer in the United States, it is the fourth most common cause of cancer-related death. Most cases are not suitable for resection and a majority is metastatic at presentation. Gemcitabine, with or without erlotinib, has been the standard chemotherapy in this setting but the benefit is only modest. Because gemcitabine has been considered a standard treatment for advanced pancreatic cancer for the past decade, several randomized trials have tested the combination of gemcitabine plus a second agent, including platinum based agents, topoisomerase inhibitors, taxanes, bevacizumab and cetuximab, as biologically “targeted” agents. At large this approach has not been successful and novel strategies are clearly needed. In this article, the authors summarizes the data from the 2011 American Society of Clinical Oncology (ASCO) Gastrointestinal Cancers Symposium, including: Abstract#175 (review of survival data in a large cohort); Abstract #286 (rapid change in prescriber patterns after the suggestion of benefit of a new regimen, FOLFIRINOX); Abstracts #238, #277, #304, and #315 (phase II trials looking at combinations that utilized EGFR blockade); Abstracts #221, #266, and #284 (phase I/II trials including VEGF blockade, anticoagulation, and traditional Chinese medicines). Image: Columbia University College of Physicians and Surgeons. New York, NY, USA. (logo)